STRATEGI PENGEMBANGAN HASIL HUTAN BUKAN KAYU DI KAWASAN HUTAN LINDUNG GUNUNG SOPUTAN KPHP UNIT V PROVINSI SULAWESI UTARA - Irene Christine Mandang; Bobby J. V. Polii; Hengki ., Walangitan (Sam Ratulangi University, 2018)
This study aims to 1) identify the potential types of NTFPs, 2) analyze the level of excellence, 3) analyze the role and influence of stakeholders and formulate superior NTFP development strategies. This research was carried out from March to July 2018, in the Unit V Gunung Soputan Protection Forest, especially in the HKm area. Tolombukan Satu Village and Liwutung Dua Village, Pasan Sub-district, Southeast Minahasa Regency, North Sulawesi Province. This research uses descriptive method, through field observation, interviews with key informants and desk study. The superior NTFP development strategy is carried out through three phases, namely the analysis of NTFP excellence levels, stakeholder analysis and SWOT analysis to formulate a strategic plan for the development of superior NTFPs. The results showed that the types of NTFPs found in the Mount Soputan HL area, namely pine (Pinus merkusii Jungh et de Virese), sugar palm (Arenga pinnata Merr), bamboo (Bamboo sp.) with class 2 level of excellence and the potential to be used as regional superior products; and candlenut (Aleurites moluccana Wild) with grade 3 excellence. From the analysis, 12 stakeholders were involved in HKm activities consisting of three primary stakeholders and nine secondary stakeholders with categories as Key players, Context setters, Subjects and Crowds. Furthermore, the superior NTFP development strategies that can be carried out are: 1) facilitation (infrastructure assistance, business capital, post-harvest handling and marketing); 2) development of nursery gardens, increase in intensive cultivation and expansion of planting areas of NTFPs; 3) mentoring, counseling, advocacy and training activities; 4) establish mutually beneficial cooperation; 5) accelerating the provision of access to area management to other forest communities. Participation, contribution, involvement and cooperation from parties related to the